2013
DOI: 10.1155/2013/148362
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Impact of Polyurethane Potting on Gun Launched Electronics

Abstract: Electronics packages in precision guided munitions are used in guidance and control units, mission computers, and fuze-safe-andarm devices. ey are subjected to high g-loads during gun launch, pyrotechnic shocks during �ight, and high g-loads upon impact with hard targets. To enhance survivability, many electronics packages are potted aer assembly. e purpose of the potting is to provide additional structural support and shock damping. Researchers at the US Army recently completed a series of dynamic mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…These models are based on the material data presented in Refs. [16,17]. For this potting, the glass transition temperature is about -10°C, which is within the usual operating range for the Army.…”
Section: Modeling the Pottingsupporting
confidence: 52%
See 1 more Smart Citation
“…These models are based on the material data presented in Refs. [16,17]. For this potting, the glass transition temperature is about -10°C, which is within the usual operating range for the Army.…”
Section: Modeling the Pottingsupporting
confidence: 52%
“…The assembly is at cold temperature (233 K) and the potting is relatively stiff due to operation below the glass transition temperature [16,17]. The Von Mises stresses in the chips near the 15,000 G force are shown in Fig.…”
Section: Case 2: Dynamic Analysis With Bonded Cold Pottingmentioning
confidence: 99%
“…In 2013, AS Haynes [162] reported a study on the reliability of the potted fuse under coupling effect of temperature and shock. The research found significant changes in the mechanical character of potting material at high temperatures (71 • C) and low temperatures (<51 • C), which affect the reliability of the system.…”
Section: Thermal-shock Couplingmentioning
confidence: 99%
“…Potting is the process of insulating the array with polymeric materials having a high bonding ability, small expansion coefficient, high mechanical endurance, and strong corrosion resistance. The array and potting materials are made into a solid whole, which is waterproof and resistant to shock and vibration [ 3 ]. Because an acoustic transducer array is the object to be potted in this study, the potting should not only ensure protection but also consider the acoustic performance.…”
Section: Introductionmentioning
confidence: 99%